Traditional society in transition : the Yemeni Jewish experience - Klorman, Bat-Zion Eraqi. (The Brill Reference Library of Judaism, 2014)
In Traditional Society in Transition: The Yemeni Jewish Experience Bat-Zion Eraqi Klorman offers an account of the unique circumstances of Yemeni Jewish existence in the wake of major changes since the second half of the nineteenth century. It follows this community's transition from a traditional patriarchal society to a group adjusting to the challenges of a modern society. Unlike the perception of the Yemeni Jews as receptive to modernity only following immigration to Palestine and Israel, Eraqi Klorman convincingly shows that some modern ideas played a role in their lives while in Yemen. Once in Palestine, they appear here as adjusting to the new conditions by striving to participate in the Zionist enterprise, consenting to secular education, transforming family practices and the status of women. "The book is an important contribution to the study of Yemeni Jews in Yemen and abroad as well as for Jewish-Muslim relations, relations between Yemeni Jews and other Jews, and gender studies...Many of these issues have not been previously studied, and the use of private archives and interviews greatly increases the value of this study.\' -Rachel Simon, Princeton University. Princeton, NJ, Association of Jewish Libraries Reviews, November/December 2014.